Preparation method of flame-retardant high-performance polypropylene and automobile foot mat prepared from flame-retardant high-performance polypropylene

By preparing polymer matrix with polymer mesh structure and nano-layer sheet structure hydrotalcite flame retardant with self-crosslinking groups, the low-temperature toughness, wear resistance and flame retardant properties of polypropylene materials are solved, and polypropylene is realized High performance improvement of composite materials.

CN119220040AInactive Publication Date: 2024-12-31GUANGZHOU CHEAN IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411490665.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polypropylene materials have limited their application range of poor toughness, poor wear resistance, poor flame retardant performance and reduced mechanical properties.

Method used

By preparing a polymer matrix with a polymer network structure, combining hydrotalcite flame retardant with a nanolayer sheet structure with self-crosslinking groups, the compatibility of polypropylene and expanded flame retardant is improved, and the compatibility of polypropylene and expandable flame retardant is improved. The negative charge action controls the dispersion of the flame retardant in the matrix to form a composite material with excellent flame retardant, mechanical properties and aging resistance.

Benefits of technology

The low-temperature toughness, wear resistance and flame retardant properties of polypropylene materials have been achieved, ensuring that the material maintains good rigidity and toughness under low temperature conditions, and has good anti-aging performance and flame retardant efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220040A_ABST
    Figure CN119220040A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of flame-retardant high-performance polypropylene and an automobile foot mat prepared from the same. The material comprises the following components in parts by weight: 100-120 parts of a polypropylene matrix; 9-12 parts of a flame retardant; 0.1 to 2.5 parts of an antioxidant; wherein the polypropylene matrix is a high-molecular polymer matrix with a net structure, which is obtained by a first copolymer formed by polymerizing an acrylic monomer and a cross-linking block copolymer; the flame retardant is a hydrotalcite flame retardant with a self-crosslinking group, the flame retardant is controlled in a matrix under the action of positive and negative charges, the dispersing performance and compatibility of the flame retardant are remarkably improved, polypropylene is endowed with excellent flame retardant property, and the mechanical property of the material is greatly improved. According to the polypropylene composite material prepared by the technical scheme, the foot mat hardened at a low temperature still has good rigidity and toughness, is not easy to deform in a treading stress process, and can be used for manufacturing an automobile foot mat.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer polypropylene composite material, belongs to the field of polymer flame-retardant plastics, and in particular to a method for preparing flame-retardant high-performance polypropylene. Background Art

[0002] As a general-purpose plastic, polypropylene has good processability, mechanical properties, low price, low specific gravity, and light weight. It is widely used in various molded products such as films, sheets, and structural parts. However, polypropylene also has disadvantages such as poor low-temperature toughness, insufficient high-temperature strength, and flammability, which greatly limits the application range of polypropylene materials. Therefore, high-performance modification of polypropylene such as reinforcement, toughening, and flame retardancy is a necessary means to expand its application field.

[0003] Adding flame retardants can effectively reduce the combustion performance of polymers. Halogen-containing flame retardants can make polypropylene products have good flame retardant properties. However, halogen-containing flame retardant products will produce a lot of black smoke during combustion, and release hydrogen halides and some carcinogens, which affect the environment and human health. Therefore, the application of halogen-containing flame retardants is greatly restricted. Some countries and organizations have banned the use of some halogen flame retardants. In this environment, halogen-free flame retardants and halogen-free flame retardant products have been greatly developed and applied.

[0004] As a halogen-free flame retardant, the intumescent flame retardant is mainly composed of salts of polyphosphoric acid or pyrophosphoric acid and nitrogen-containing compounds. When burning, it forms a surface expansion layer to inhibit the diffusion and heat transfer of decomposition products, thereby exerting flame retardancy. However, halogen-free flame retardants often need to be added to the base resin in large quantities to have a good flame retardant effect. The mechanical properties of halogen-free flame retardant products are even far lower than those of the base resin, which will seriously affect the mechanical properties of the resin, thereby damaging the original physical properties of the resin. Polypropylene has poor antistatic properties, and after conventional flame retardant and antistatic modification, the mechanical properties of the product are significantly reduced. Therefore, the mechanical properties, wear resistance and anti-aging properties of the flame retardant and antistatic polypropylene obtained in the end are significantly reduced, limiting its service life.

[0005] For the reinforcement of mechanical properties, one improved method is to increase the melt strength of polypropylene, that is, to increase the molecular weight of polypropylene, but this will bring difficulties in material melting and extrusion. Another method is to widen the molecular weight distribution. For example, US7365136 and US6875826 reported a method for preparing homopolymer and random copolymer polypropylene with wide molecular weight distribution and high melt strength, which selected alkoxysilane as an external electron donor (such as dicyclopentyldimethoxysilane) and regulated the molecular weight and distribution by adjusting the hydrogen concentration in multiple series-connected reactors to achieve the effect of improving the melt strength of polypropylene.

[0006] Alternatively, by improving the expansion flame retardant, the compatibility of the flame retardant with the polypropylene matrix is ​​improved. The Chinese patent with publication number CN107915901A discloses a polypropylene environmentally friendly flame retardant foam material and its preparation method, including the following raw materials: diatomaceous earth, polypropylene, foaming agent, nano-TiO2, phosphorus-based expansion flame retardant, carboxylated polypropylene, diisopropylbenzene peroxide, silane coupling agent, titanate coupling agent, zirconate coupling agent, stearic acid. The phosphorus-based expansion flame retardant used is an environmentally friendly green flame retardant, and its system itself has a synergistic effect, has excellent flame retardant properties, and produces low smoke, low toxicity, and no corrosive gas. This method combines the flame retardant with the main chain or side chain of polypropylene by chemical methods, so that the modified polypropylene has flame retardancy and significantly improves compatibility with the matrix, but the preparation process is complicated and the cost is high.

[0007] The Chinese patent with publication number CN111040293B discloses an expanded flame-retardant polypropylene and a preparation method thereof. The expanded flame-retardant polypropylene comprises the following components by mass: 70-100 parts of polypropylene, 10-30 parts of an expanded flame retardant, 1-5 parts of modified nano-silicon dioxide, and 0-0.2 parts of an antioxidant; wherein the modified nano-silicon dioxide is a nano-silicon dioxide grafted and modified by a triazine derivative containing phenyl and triazine groups. The preparation method of the expanded flame-retardant polypropylene comprises the following steps: according to the composition ratio, polypropylene, an expanded flame retardant, modified nano-silicon dioxide and an antioxidant are mixed, and the mixture is placed in a reactor for melt blending. The expanded flame-retardant polypropylene reinforced with modified nano-silicon dioxide of the invention has excellent flame retardant properties. However, the expanded flame retardant in the prior art still has problems such as poor water resistance, poor low-temperature toughness, and poor wear resistance.

[0008] Therefore, developing a polypropylene composite material whose components have good thermal stability and polymer compatibility, uniform dispersion of the components, not easy to precipitate, can make the material achieve long-term flame retardancy, and has good low-temperature toughness, excellent mechanical properties, wear resistance and durability is a current research hotspot. Summary of the invention

[0009] In order to solve the above problems, the purpose of the present invention is to provide a method for preparing flame-retardant high-performance polypropylene to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.

[0010] The purpose of the present invention is achieved through the following technical scheme: a flame retardant high-performance polypropylene material, which is prepared from the following raw materials in parts by mass: 100-120 parts of a polypropylene matrix; 9-12 parts of a flame retardant; 0.1-2.5 parts of an antioxidant; the polypropylene matrix is ​​a high molecular network structure polymer matrix obtained by polymerizing a first copolymer formed by polymerizing acrylic acid monomers and cross-linking block copolymers; the block copolymer is a styrene-butadiene-styrene block copolymer.

[0011] According to one aspect of the present invention, in order to achieve the above object, firstly, a polypropylene matrix with good low-temperature toughness and significantly improved elasticity is prepared, which specifically comprises the following steps:

[0012] S001: In a reaction kettle, isooctyl acrylate, dimethylamino methacrylate, hydroxypropyl acrylate and n-dodecyl mercaptan are stirred evenly, and the temperature is slowly raised to 110-150° C. under nitrogen protection, and then an initiator azobisisobutyronitrile is added dropwise. After fully reacting for 150-200 minutes, acrylic acid is added and the reaction is continued for 100-150 minutes to obtain a first high molecular weight copolymer with an average molecular weight of 50,000-60,000, and hydroxyl groups and amine groups are grafted on the side chains;

[0013] S002, adding the first copolymer and the block copolymer into a reaction kettle, raising the temperature to 200-220° C. under nitrogen protection, stirring at a speed of 500 rpm, dispersing the block copolymer in the high molecular weight first copolymer, and continuing the reaction for 60-80 minutes to obtain a high molecular weight network structure polymer matrix;

[0014] The mass fraction of the dimethylamino methacrylate is 50-60 parts, the mass fraction of isooctyl acrylate is 10-20 parts, the mass fraction of acrylic acid is 20-30 parts, the mass fraction of hydroxypropyl acrylate is 50-60 parts, the mass fraction of n-dodecyl mercaptan is 1.0-2.5 parts, and the mass fraction of azobisisobutyronitrile is 2.0-4.0 parts;

[0015] The mass ratio of the block copolymer to the first copolymer is 2 to 4:10; the molecular weight of the block copolymer is 60,000 to 70,000;

[0016] The flame retardant polypropylene is obtained by melt blending 100 parts of polypropylene matrix, 9 parts of flame retardant and 0.5 parts of antioxidant. We found that the flame retardant polypropylene obtained in this way has improved low temperature performance due to its high molecular weight network structure polymer, and the obtained matrix has good elasticity and is easy to recover after deformation, which improves the problem that polypropylene will become hard, brittle and easy to break under low temperature conditions. However, we found that the styrene-butadiene-styrene block copolymer is directly dispersed in the polypropylene copolymer, and the dispersion is uneven, and there will be problems such as poor thermal stability, poor aging resistance and poor mechanical properties. In addition, the expansion flame retardant is not compatible with the matrix, and a series of problems such as precipitation occur, which seriously affect the flame retardant properties of the material.

[0017] Therefore, we modified the styrene-butadiene-styrene block copolymer, hoping to improve its compatibility with flame retardants and aging resistance on the basis of improving its mechanical properties. Specifically:

[0018] S101, dissolving styrene-butadiene-styrene block copolymer in 150 mL of ethyl acetate, stirring at a temperature of 60 to 70° C., then dropping N,N-dimethylhexadecyl-1-amine into the completely dissolved styrene-butadiene-styrene block copolymer solution, reacting for 24 to 30 hours, and after the reaction, pouring the reaction solution into petroleum ether, precipitating and washing three times, and finally drying in a 60° C. oven to obtain a light yellow solid product;

[0019] S102, dissolving N,N-dimethylformamide in deionized water at a temperature of 60°C, then slowly adding a light yellow solid product and reacting at 45°C for 30 hours; after the reaction is completed, filtering the impurities in the mixed solution to obtain a clear and slightly viscous filtrate, drying it in an oven at 35°C, and washing it with deionized water for multiple times to obtain a diamine block copolymer, the surface of the copolymer has a positive charge; wherein, the ratio of N,N-dimethylhexadecyl-1-amine to styrene-butadiene-styrene block copolymer is 1:10; the ratio of N,N-dimethylhexadecyl-1-amine to N,N-dimethylformamide is 1:2.

[0020] Due to the opposite polarity between polypropylene and intumescent flame retardant particles, the intumescent flame retardant has poor compatibility and uneven dispersion in polypropylene, which causes the intumescent flame retardant to easily agglomerate, reducing the flame retardant properties and mechanical properties. In order to avoid these shortcomings, conventional intumescent flame retardants are compounded with a small amount of nanoparticles to improve the flame retardant properties and mechanical properties of polypropylene at the same time. These nano additives can induce the formation of a protective carbon layer rich in inorganic substances, thereby improving the flame retardancy and the mechanical properties of the material. However, it is necessary to use a coupling agent to surface treat the nanoparticles to improve the dispersibility of the nanoparticles in the polypropylene matrix. Because most organic coupling agents are highly flammable, the flame retardant properties of the final material are not ideal.

[0021] The first copolymer contained in the polypropylene matrix has hydroxyl and amine groups grafted on its side chains. These small molecular polar substances have the defect of poor dispersion in the non-polar matrix of polypropylene. With the increase of use time, the small molecules of polar carbon source are easy to migrate to the surface of the material, so that the carbon source is unevenly dispersed in the polypropylene matrix, which reduces the flame retardant performance of the material. In addition, the small molecules of polar carbon source have poor compatibility with non-polar polypropylene, which further causes the mechanical properties of polypropylene flame retardant materials to further decline. Therefore, we choose inorganic materials containing anions with negative charges as flame retardants, so that the flame retardants and these polar substances in the matrix interact and restrict each other, which not only improves the compatibility of the flame retardant with the matrix, but also through the action of positive and negative charges, the flame retardant and small molecular polar substances are firmly controlled in the matrix, making it difficult for them to precipitate.

[0022] Therefore, we prepared a flame retardant, which can effectively solve the problems of unsatisfactory dispersibility and flame retardant effect, and can effectively solve the problem of flame retardant precipitation. The flame retardant is a hydrotalcite flame retardant with a self-crosslinking group. The flame retardant has a unique nano-sheet structure and is an organic-inorganic hybrid material. It also has a carbon source, an acid source and a gas source. The hydrotalcite is hydrophilic and has the problem of easy precipitation during use. Therefore, it is organically modified to improve its hydrophobic properties and compatibility with polymers. The specific preparation method is as follows:

[0023] S201, drying the hydrotalcite at 80°C for 5 hours, then heating the hydrotalcite to 90°C in a mixed solution of nitric acid and sodium nitrate, stirring and soaking for 2 hours, after the reaction is completed, filtering, washing with anhydrous ethanol for 3 times, and drying at 80°C for 20 hours to obtain hydrotalcite with enlarged interlayer spacing. Then, glycine is added to the hydrotalcite with enlarged interlayer spacing, reacted at 60-80°C for 24 hours, and a suspension is obtained, wherein the volume ratio of nitric acid to sodium nitrate is 1:10, the concentration of nitric acid is 0.5 mol / L, and the concentration of sodium nitrate is 1.2 mol / L; the mass ratio of hydrotalcite to the mixed solution of nitric acid and sodium nitrate is 1:1; the mass ratio of glycine to hydrotalcite is 2-3:10;

[0024] S202, adding dodecyl phosphate and phytic acid to the suspension, stirring and reacting at 60-80°C for 6-8 hours to obtain a reaction solution; adjusting the pH to neutral with citric acid, obtaining a product with a rotary evaporator, and drying the product in an oven at 80°C for 12 hours to obtain a white solid containing a large amount of anions in the intercalation layer; dispersing the white solid in deionized water to obtain a dispersion; the mass ratio of dodecyl phosphate, phytic acid and hydrotalcite is 2-3:3-4:10;

[0025] S203, add azobenzene-4,4-dicarboxylic acid to deionized water, stir evenly, add sodium hydroxide solution, adjust the pH value to 8.5, mix the dispersion with the azobenzene-4,4-dicarboxylic acid after adjusting the pH, pass N2 protection at room temperature, and react for 24 hours. Filter the liquid after the reaction to obtain a light yellow filter cake, wash the filter cake with deionized water and ethanol 3-4 times respectively, dry it in a vacuum oven at 60°C, and grind it to obtain a light yellow solid, which is a hydrotalcite flame retardant with a nano-lamellar structure with self-crosslinking groups; the mass ratio of azobenzene-4,4-dicarboxylic acid to hydrotalcite is 1:5.

[0026] The interlayer anions of hydrotalcite interact with the positively charged layers by weak electrostatic attraction, hydrogen bonds and van der Waals forces. Therefore, the interlayer anions of hydrotalcite can be changed by ion exchange, among which NO3 - It is the most easily exchanged anion. The higher the valence of the anion, the easier it is to enter the interlayer of hydrotalcite through ion exchange. Therefore, we use dodecyl phosphate and inositol hexaphosphate to make the phosphate anion replace NO3 - The intercalation enters the interlayer of hydrotalcite, and the intercalated hydrotalcite can provide carbon source and acid source at the same time. At the same time, azobenzene-4,4-dicarboxylic acid is grafted onto the hydrotalcite, so that the flame retardant contains flame retardant element nitrogen, has high temperature self-crosslinking groups (N=N), and can generate low-energy free radicals after heating, so that it can play a role in both gas phase and condensed phase. The grafted hydrotalcite is also a highly efficient ultraviolet absorber, which can improve the anti-aging performance of the composite material. More importantly, it has better compatibility with the polymer matrix and flame retardant efficiency.

[0027] Furthermore, a flame retardant high-performance polypropylene composite material is prepared, specifically:

[0028] Add flame retardant, polypropylene matrix and antioxidant into a mixer, melt blend, mix at a temperature of 190-220°C, for 20-40 minutes, at a rotation speed of 100 rpm, and obtain a mixed product, which is flame retardant high-performance polypropylene.

[0029] In order to obtain a polypropylene composite material with high melt strength, high rigidity and toughness, it is very important to control the composition, structure or performance of the dispersed phase and the continuous phase. The present invention can prepare a polypropylene composite material that is conducive to achieving the purpose of the present invention through these preferred conditions, thereby obtaining a polypropylene composite material with better performance.

[0030] Finally, a car floor mat was prepared using this flame-retardant high-performance polypropylene, and the prepared mixed product was injection molded using an injection molding machine to obtain a flat plate sample with a thickness of 4 mm, a length of 400 mm, and a width of 400 mm.

[0031] The car mat made of polypropylene according to the present invention has good flame retardant and antistatic properties, as well as low-temperature rigidity and toughness. After the car mat is deformed, it can quickly return to its original state when the external force is removed. Especially under low temperature conditions below minus 30°C, the hardened mat still has good rigidity and toughness, is not easy to deform during the pedaling force process, and will not interfere with the accelerator and brake pedals, ensuring safe driving.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1) The present invention provides a flame-retardant high-performance polypropylene composite material, which is polymerized into a high molecular weight first copolymer by several acrylic acid monomers, a cross-linked diamine block copolymer as a continuous phase, and a hydrotalcite flame retardant with a self-cross-linking group and a nano-lamellar structure intercalated with a large number of anions as a dispersed phase. Through the action of positive and negative charges, the flame retardant and polar small molecules are firmly controlled in the matrix, and its dispersion performance and compatibility are significantly improved, thereby obtaining a composite material with good compatibility and excellent mechanical properties. The material has good wear resistance, good flame retardancy, good heat deformation resistance, and good low-temperature flexibility. Due to its special material compounding, the composite material can also absorb ultraviolet light and has good aging resistance. The composite material can be widely used in public places, automotive interiors, decorations and other fields with strict requirements on flame retardancy and smoke emission, and can especially be used as a flame retardant product under high-intensity stress.

[0034] 2) The present invention provides a hydrotalcite flame retardant with a self-crosslinking group and a nano-lamellar structure intercalated with a large number of anions. The flame retardant has a unique nano-lamellar structure and is an organic-inorganic hybrid material. It also has a carbon source, an acid source and a gas source, and can provide long-term and efficient flame retardancy. At the same time, the materials used are all environmentally friendly materials and do not cause any harm to the environment and human body.

[0035] 3) The present invention also provides a foot pad, which has high softness. The foot pad made of the composite material prepared by the present invention can reach a softness of 60° and has good weather resistance. It can be used all year round, that is, it can resist cold in winter and high temperature in summer. It will not produce cracking. There is no odor at relatively high temperatures. It has high strength and long service life. The tensile strength of the composite material of the present invention reaches 14MPa, and it has good anti-skid safety. The composite material of the present invention can produce stronger grip, prevent slipping, and ensure driving safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 , is a field emission scanning electron micrograph of the hydrotalcite flame retardant with a nano-lamellar structure having a self-crosslinking group prepared in Example 1. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content described in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0038] Example 1

[0039] A flame retardant high-performance polypropylene composite material, firstly preparing a polypropylene matrix, specifically:

[0040] In a reaction kettle, 20 parts of isooctyl acrylate, 50 parts of dimethylamino methacrylate, 50 parts of hydroxypropyl acrylate, and 2.0 parts of n-dodecyl mercaptan were stirred evenly, and the temperature was slowly raised to 110° C. under nitrogen protection, and then 3.0 parts of azobisisobutyronitrile as an initiator was added dropwise. After fully reacting for 1200 minutes, 30 parts of acrylic acid were added and the reaction was continued for 150 minutes to obtain a first copolymer with an average molecular weight of 52378, and hydroxyl groups and amine groups were grafted on the side chains;

[0041] S002, adding 50 parts of the first copolymer and 10 parts of the block copolymer with an average molecular weight of 60,000 into a reaction kettle, heating to 200° C. under nitrogen protection, stirring at a speed of 500 rpm, so that the block copolymer is dispersed in the high molecular weight first copolymer, and the reaction is continued for 80 minutes to obtain a high molecular weight network structure polymer matrix;

[0042] Further, a hydrotalcite flame retardant with a self-crosslinking group is prepared, specifically:

[0043] 50 ml of 1 mol / L nitric acid and 500 ml of sodium nitrate are uniformly mixed to obtain an acid mixture; 50 parts of hydrotalcite are dried at 80° C. for 5 hours, and then the hydrotalcite is heated to 90° C. in 50 parts of the acid mixture, stirred and soaked for 2 hours, and after the reaction is completed, filtered, washed with anhydrous ethanol 3 times, and dried at 80° C. for 20 hours to obtain hydrotalcite with enlarged interlayer spacing; then 10 parts of glycine and 50 parts of deionized water are added to the hydrotalcite with enlarged interlayer spacing, and reacted at 80° C. for 24 hours to obtain a suspension;

[0044] 10 parts of dodecyl phosphoric acid and 15 parts of inositol hexaphosphate are added to the suspension, stirred and reacted at 80°C for 8 hours to obtain a reaction solution; the pH is adjusted to neutral with citric acid, a product is obtained by a rotary evaporator, and the product is dried in an oven at 80°C for 12 hours to obtain a white solid containing a large amount of anions in the intercalation layer; the white solid is dispersed in deionized water to obtain a dispersion;

[0045] 10 parts of azobenzene-4,4-dicarboxylic acid are added to deionized water, stirred evenly, and sodium hydroxide solution is added to adjust the pH value to 8.5, the dispersion is mixed with the azobenzene-4,4-dicarboxylic acid after the pH is adjusted, N2 protection is introduced at room temperature, and the reaction is carried out for 24 hours; the mixed solution after the reaction is filtered to obtain a light yellow filter cake, the filter cake is washed with deionized water and ethanol for 3 times respectively, dried in a vacuum oven at 60°C, and then ground to obtain a light yellow solid, which is a hydrotalcite flame retardant with a nano-lamellar structure with a self-crosslinking group.

[0046] Finally, 12 parts of a nano-lamellar structured hydrotalcite flame retardant with a self-crosslinking group, 100 parts of a high molecular weight network structure polymer matrix and 2 parts of an antioxidant were added to a mixer and melt blended at a mixing temperature of 190°C for 20 minutes at a speed of 100 rpm to obtain a flame-retardant high-performance polypropylene.

[0047] A car floor mat was prepared using the flame-retardant high-performance polypropylene, and the prepared mixed product was injection molded using an injection molding machine to obtain a flat plate sample with a thickness of 4 mm, a length of 400 mm, and a width of 400 mm.

[0048] Example 2

[0049] A flame-retardant high-performance polypropylene composite material requires the preparation of a polypropylene matrix. To prepare the polypropylene matrix, a diamine-modified block copolymer is first prepared, which is obtained by modifying a styrene-butadiene-styrene block copolymer. The preparation method is as follows:

[0050] 100 parts of styrene-butadiene-styrene block copolymer were dissolved in 100 parts of ethyl acetate, and stirred evenly at a temperature of 70°C. Then 10 parts of N,N-dimethylhexadecyl-1-amine were added dropwise to the completely dissolved styrene-butadiene-styrene block copolymer solution, and the reaction was carried out for 30 hours. After the reaction was completed, the reaction solution was poured into petroleum ether, precipitated and washed three times, and finally dried in an oven at 60°C to obtain a light yellow solid product;

[0051] 20 parts of N,N-dimethylformamide were dissolved in 100 parts of deionized water at a temperature of 60°C, and then 110 parts of light yellow solid product were slowly added and reacted at 45°C for 30 hours; after the reaction was completed, the impurities in the mixed solution were filtered to obtain a clear and slightly viscous filtrate, which was dried in an oven at 35°C and washed with deionized water for several times to obtain a diamine block copolymer with a positive charge on the surface of the copolymer.

[0052] Further, a polypropylene matrix is ​​prepared, specifically

[0053] In a reaction kettle, 20 parts of isooctyl acrylate, 50 parts of dimethylamino methacrylate, 50 parts of hydroxypropyl acrylate and 2.0 parts of n-dodecyl mercaptan were stirred evenly, and the temperature was slowly raised to 110° C. under nitrogen protection, and then 3.0 parts of azobisisobutyronitrile as an initiator was added dropwise. After fully reacting for 200 minutes, 30 parts of acrylic acid were added and the reaction was continued for 150 minutes to obtain a first copolymer with an average molecular weight of 53015, and hydroxyl groups and amine groups were grafted on the side chains;

[0054] S002, add 50 parts of the first copolymer and 10 parts of the diamine block copolymer into the reactor, and under nitrogen protection, heat up to 200°C, stir at 500 rpm, and allow the diamine block copolymer to continue to react in the high molecular weight first copolymer for 80 minutes to obtain a high molecular weight network structure polymer matrix.

[0055] Further, a hydrotalcite flame retardant with a self-crosslinking group is prepared, specifically:

[0056] 50 ml of 1 mol / L nitric acid and 500 ml of sodium nitrate are uniformly mixed to obtain an acid mixture; 50 parts of hydrotalcite are dried at 80° C. for 5 hours, and then the hydrotalcite is heated to 90° C. in 50 parts of the acid mixture, stirred and soaked for 2 hours, and after the reaction is completed, filtered, washed with anhydrous ethanol 3 times, and dried at 80° C. for 20 hours to obtain hydrotalcite with enlarged interlayer spacing; then 10 parts of glycine and 50 parts of deionized water are added to the hydrotalcite with enlarged interlayer spacing, and reacted at 80° C. for 24 hours to obtain a suspension;

[0057] 10 parts of dodecyl phosphoric acid and 15 parts of inositol hexaphosphate are added to the suspension, stirred and reacted at 80°C for 8 hours to obtain a reaction solution; the pH is adjusted to neutral with citric acid, a product is obtained by a rotary evaporator, and the product is dried in an oven at 80°C for 12 hours to obtain a white solid containing a large amount of anions in the intercalation layer; the white solid is dispersed in deionized water to obtain a dispersion;

[0058] 10 parts of azobenzene-4,4-dicarboxylic acid are added to deionized water, stirred evenly, and sodium hydroxide solution is added to adjust the pH value to 8.5, the dispersion is mixed with the azobenzene-4,4-dicarboxylic acid after the pH is adjusted, N2 protection is introduced at room temperature, and the reaction is carried out for 24 hours; the mixed solution after the reaction is filtered to obtain a light yellow filter cake, the filter cake is washed with deionized water and ethanol for 3 times respectively, and the filter cake is dried in a vacuum oven at 60°C and then ground to obtain a light yellow solid, which is a hydrotalcite flame retardant with a nano-lamellar structure with self-crosslinking groups.

[0059] Finally, 12 parts of a nano-lamellar structured hydrotalcite flame retardant with a self-crosslinking group, 100 parts of a high molecular weight network structure polymer matrix and 2 parts of an antioxidant were added to a mixer and melt blended at a mixing temperature of 190°C for 20 minutes at a speed of 100 rpm to obtain a flame-retardant high-performance polypropylene.

[0060] A car floor mat was prepared using the flame-retardant high-performance polypropylene, and the prepared mixed product was injection molded using an injection molding machine to obtain a flat plate sample with a thickness of 4 mm, a length of 400 mm, and a width of 400 mm.

[0061] Example 3

[0062] A flame-retardant high-performance polypropylene composite material requires the preparation of a polypropylene matrix. To prepare the polypropylene matrix, a diamine-modified block copolymer is first prepared, which is obtained by modifying a styrene-butadiene-styrene block copolymer. The preparation method is as follows:

[0063] 100 parts of styrene-butadiene-styrene block copolymer were dissolved in 100 parts of ethyl acetate, and stirred evenly at a temperature of 70°C. Then 10 parts of N,N-dimethylhexadecyl-1-amine were added dropwise to the completely dissolved styrene-butadiene-styrene block copolymer solution, and the reaction was carried out for 30 hours. After the reaction was completed, the reaction solution was poured into petroleum ether, precipitated and washed three times, and finally dried in an oven at 60°C to obtain a light yellow solid product;

[0064] 20 parts of N,N-dimethylformamide were dissolved in 100 parts of deionized water at a temperature of 60°C, and then 110 parts of light yellow solid product were slowly added and reacted at 45°C for 30 hours; after the reaction was completed, the impurities in the mixed solution were filtered to obtain a clear and slightly viscous filtrate, which was dried in an oven at 35°C and washed with deionized water for several times to obtain a diamine block copolymer with a positive charge on the surface of the copolymer.

[0065] Further, a polypropylene matrix is ​​prepared, specifically

[0066] In a reaction kettle, 10 parts of isooctyl acrylate, 60 parts of dimethylamino methacrylate, 60 parts of hydroxypropyl acrylate, and 2.0 parts of n-dodecyl mercaptan were stirred evenly, and the temperature was slowly raised to 110° C. under nitrogen protection, and then 4.0 parts of azobisisobutyronitrile as an initiator was added dropwise. After fully reacting for 200 minutes, 20 parts of acrylic acid were added and the reaction was continued for 150 minutes to obtain a first copolymer with an average molecular weight of 58734, and hydroxyl groups and amine groups were grafted on the side chains;

[0067] S002, add 50 parts of the first copolymer and 20 parts of the diamine block copolymer into the reactor, and under nitrogen protection, heat up to 200°C, stir at 500 rpm, and allow the diamine block copolymer to continue to react in the high molecular weight first copolymer for 80 minutes to obtain a high molecular weight network structure polymer matrix.

[0068] Further, a hydrotalcite flame retardant with a self-crosslinking group is prepared, specifically:

[0069] 50 ml of 1 mol / L nitric acid and 500 ml of sodium nitrate are uniformly mixed to obtain an acid mixture; 50 parts of hydrotalcite are dried at 80° C. for 5 hours, then the hydrotalcite is heated to 90° C. in 50 parts of the acid mixture, stirred and soaked for 2 hours, after the reaction is completed, filtered, washed with anhydrous ethanol 3 times, and dried at 80° C. for 20 hours to obtain hydrotalcite with enlarged interlayer spacing; then 10 parts of glycine and 50 parts of deionized water are added to the hydrotalcite with enlarged interlayer spacing, reacted at 80° C. for 24 hours to obtain a suspension, the volume ratio of nitric acid to sodium nitrate is 1:10, the concentration of nitric acid is 0.5 mol / L, and the concentration of sodium nitrate is 1.2 mol / L; the mass ratio of hydrotalcite to the mixture of nitric acid and sodium nitrate is 1:1; the mass ratio of glycine to hydrotalcite is 2-3:10;

[0070] 10 parts of dodecyl phosphoric acid and 20 parts of inositol hexaphosphate are added to the suspension, stirred and reacted at 80°C for 8 hours to obtain a reaction solution; the pH is adjusted to neutral with citric acid, a product is obtained by a rotary evaporator, and the product is dried in an oven at 80°C for 12 hours to obtain a white solid containing a large amount of anions in the intercalation layer; the white solid is dispersed in deionized water to obtain a dispersion;

[0071] 10 parts of azobenzene-4,4-dicarboxylic acid are added to deionized water, stirred evenly, and sodium hydroxide solution is added to adjust the pH value to 8.5, the dispersion is mixed with the azobenzene-4,4-dicarboxylic acid after the pH is adjusted, N2 protection is introduced at room temperature, and the reaction is carried out for 24 hours; the mixed solution after the reaction is filtered to obtain a light yellow filter cake, the filter cake is washed with deionized water and ethanol for 3 times respectively, dried in a vacuum oven at 60°C, and then ground to obtain a light yellow solid, which is a hydrotalcite flame retardant with a nano-lamellar structure with a self-crosslinking group.

[0072] Finally, 9 parts of a nano-lamellar structured hydrotalcite flame retardant with a self-crosslinking group, 100 parts of a high molecular weight network structure polymer matrix and 2 parts of an antioxidant were added to a mixer and melt blended at a mixing temperature of 190°C for 20 minutes at a rotation speed of 100 rpm to obtain a flame-retardant high-performance polypropylene.

[0073] A car floor mat was prepared using the flame-retardant high-performance polypropylene, and the prepared mixed product was injection molded using an injection molding machine to obtain a flat plate sample with a thickness of 4 mm, a length of 400 mm, and a width of 400 mm.

[0074] Example 4

[0075] A flame-retardant high-performance polypropylene composite material requires the preparation of a polypropylene matrix. To prepare the polypropylene matrix, a diamine-modified block copolymer is first prepared, which is obtained by modifying a styrene-butadiene-styrene block copolymer. The preparation method is as follows:

[0076] 100 parts of styrene-butadiene-styrene block copolymer were dissolved in 100 parts of ethyl acetate, and stirred evenly at a temperature of 70°C. Then 10 parts of N,N-dimethylhexadecyl-1-amine were added dropwise to the completely dissolved styrene-butadiene-styrene block copolymer solution, and the reaction was carried out for 30 hours. After the reaction was completed, the reaction solution was poured into petroleum ether, precipitated and washed three times, and finally dried in an oven at 60°C to obtain a light yellow solid product;

[0077] 20 parts of N,N-dimethylformamide were dissolved in 100 parts of deionized water at a temperature of 60°C, and then 110 parts of light yellow solid product were slowly added and reacted at 45°C for 30 hours; after the reaction was completed, the impurities in the mixed solution were filtered to obtain a clear and slightly viscous filtrate, which was dried in an oven at 35°C and washed with deionized water for several times to obtain a diamine block copolymer with a positive charge on the surface of the copolymer; wherein the ratio of N,N-dimethylhexadecyl-1-amine to styrene-butadiene-styrene block copolymer was 1:10; the ratio of N,N-dimethylhexadecyl-1-amine to N,N-dimethylformamide was 1:2.

[0078] Further, a polypropylene matrix is ​​prepared, specifically

[0079] In a reaction kettle, 10 parts of isooctyl acrylate, 60 parts of dimethylamino methacrylate, 60 parts of hydroxypropyl acrylate, and 2.0 parts of n-dodecyl mercaptan were stirred evenly, and the temperature was slowly raised to 110° C. under nitrogen protection, and then 4.0 parts of azobisisobutyronitrile as an initiator was added dropwise. After fully reacting for 200 minutes, 20 parts of acrylic acid were added and the reaction was continued for 150 minutes to obtain a first copolymer with an average molecular weight of 58196, and hydroxyl groups and amine groups were grafted on the side chains;

[0080] S002, add 50 parts of the first copolymer and 20 parts of the diamine block copolymer into the reactor, and under nitrogen protection, heat up to 200°C, stir at 500 rpm, and allow the diamine block copolymer to continue to react in the high molecular weight first copolymer for 80 minutes to obtain a high molecular weight network structure polymer matrix.

[0081] Further, a hydrotalcite flame retardant with a self-crosslinking group is prepared, specifically:

[0082] 50 ml of 1 mol / L nitric acid and 500 ml of sodium nitrate are uniformly mixed to obtain an acid mixture; 50 parts of hydrotalcite are dried at 80° C. for 5 hours, and then the hydrotalcite is heated to 90° C. in 50 parts of the acid mixture, stirred and soaked for 2 hours, and after the reaction is completed, filtered, washed with anhydrous ethanol 3 times, and dried at 80° C. for 20 hours to obtain hydrotalcite with an enlarged interlayer spacing; then 15 parts of glycine and 50 parts of deionized water are added to the hydrotalcite with an enlarged interlayer spacing, and reacted at 80° C. for 24 hours to obtain a suspension;

[0083] 15 parts of dodecyl phosphoric acid and 15 parts of inositol hexaphosphate are added to the suspension, stirred and reacted at 80°C for 8 hours to obtain a reaction solution; the pH is adjusted to neutral with citric acid, a product is obtained by a rotary evaporator, and the product is dried in an oven at 80°C for 12 hours to obtain a white solid containing a large amount of anions in the intercalation layer; the white solid is dispersed in deionized water to obtain a dispersion;

[0084] 10 parts of azobenzene-4,4-dicarboxylic acid are added to deionized water, stirred evenly, and sodium hydroxide solution is added to adjust the pH value to 8.5, the dispersion is mixed with the azobenzene-4,4-dicarboxylic acid after the pH is adjusted, N2 protection is introduced at room temperature, and the reaction is carried out for 24 hours; the mixed solution after the reaction is filtered to obtain a light yellow filter cake, the filter cake is washed with deionized water and ethanol for 3 times respectively, and the filter cake is dried in a vacuum oven at 60°C and then ground to obtain a light yellow solid, which is a hydrotalcite flame retardant with a nano-lamellar structure with a self-crosslinking group, and the mass ratio of azobenzene-4,4-dicarboxylic acid to hydrotalcite is 1:5.

[0085] Finally, 11 parts of a nano-lamellar structured hydrotalcite flame retardant with a self-crosslinking group, 120 parts of a high molecular weight network structure polymer matrix and 2 parts of an antioxidant were added to a mixer and melt blended at a mixing temperature of 190°C for 20 minutes at a rotation speed of 100 rpm to obtain a flame-retardant high-performance polypropylene.

[0086] A car mat was prepared using the flame-retardant high-performance polypropylene, and the prepared mixed product was injection molded by an injection molding machine to obtain a flat plate sample with a thickness of 4 mm, a length of 400 mm, and a width of 400 mm. Comparative Example 1, the non-crosslinked block copolymer in the polypropylene matrix was directly replaced by an equal amount of the first copolymer, and the rest was the same as Example 2;

[0087] In comparative example 2, the flame retardant is directly replaced by an equal amount of natural hydrotalcite, and the other aspects are the same as those in Example 2; in comparative example 3, the flame retardant is not azobenzene-4,4-dicarboxylic acid grafted hydrotalcite, and does not have a self-crosslinking group, and the other aspects are the same as those in Example 2;

[0088] Comparative Example 4: the non-crosslinked block copolymer in the polypropylene matrix is ​​directly replaced by the first copolymer in equal amount, the flame retardant is directly replaced by natural hydrotalcite in equal amount, and the rest is the same as in Example 2.

[0089] Experimental effect comparison data

[0090] 1) Scanning electron microscopy

[0091] The morphology of the hydrotalcite flame retardant with a nano-lamellar structure having a self-crosslinking group in Example 2 was observed using a field emission scanning electron microscope. Before the test, the flame retardant sample in Example 1 was evenly dispersed on the conductive adhesive, and the scanning electron microscope parameters were adjusted, with an acceleration voltage of 3.0 kV and a magnification of 1000 times. The morphology is shown in FIG. Figure 1 ,from Figure 1 It can be seen that the flame retardant is a unique nano-sheet structure with small size and relatively uniform dispersion. Due to the rich anions on the surface, there is a slight mutual attraction between the local parts. After being added to the cationic polypropylene matrix, due to the effect of positive and negative charges, it will reduce agglomeration and be evenly dispersed in the matrix.

[0092] 2) Mechanical properties test of polypropylene composites

[0093] The flat plate samples prepared in Examples 1-4 and Comparative Examples 1-4 were cut into a sample test size of 300*300mm. The thickness of the middle part of the sample was measured three times with a spiral micrometer before testing and the average value was taken. Then the two ends of the sample were clamped at the two ends of the fixture. At room temperature, the stretching speed was set to 10mm / min, and the tensile strength (Ts) and elongation at break (Eb) of the sample to be tested were tested. The samples of Examples 1-4 and Comparative Examples 1-4 were tested for hardness and cold resistance, as shown in Table 1. As can be seen from Table 1, in Examples 1-4, after the cross-linked block copolymer in the polypropylene matrix, because of the selection of soft and hard materials combined, the close combination of the continuous phase and the dispersed phase, the hardness of the polypropylene composite material finally obtained was reduced, but its tensile strength and elongation at break were significantly improved. Moreover, after the cross-linked modified diamine block copolymer, its low temperature resistance was significantly improved.

[0094] Table 1 Mechanical properties test record of polypropylene composite materials

[0095]

[0096] 3) Elasticity test and anti-aging performance test of polypropylene composite materials

[0097] The samples of Examples 1-4 and Comparative Examples 1-4 were subjected to elasticity test and anti-aging performance test, and the results are shown in Table 2;

[0098] The elasticity test adopts the following test method: Sample test size: 300*300mm, temperature: minus 30℃, constant temperature time: 24 hours Test steps: Divide the cut samples into two groups, each with 3 parallel samples, one group is curled along the injection direction of the product, and the other group is curled perpendicular to the injection direction. Curl them into a cylinder with a diameter of 80mm in turn, fix them with rubber bands and place them in an oven at minus 30℃ for 24 hours. After the constant temperature curling is completed, quickly untie the binding rubber bands and let them spread freely horizontally in the oven, and keep the temperature unchanged. Measure the distance h from the edge of the sample to the horizontal support surface after 25 minutes. The smaller the distance h, the better the deformation recovery of the sample material. Generally, h≤5mm is considered qualified.

[0099] The anti-aging performance test is to subject the sample to a 1000h xenon lamp accelerated aging experiment, compare the fracture strength before and after the aging test, and obtain the fracture strength retention rate; as can be seen from Table 2, in Example 2-4, because the first copolymer with high molecular weight is polymerized from acrylic acid monomer, the cross-linked diamine block copolymer is used as the continuous phase, and the hydrotalcite flame retardant with a self-crosslinking group and a large number of anions intercalated in the nano-lamellar structure is used as the dispersed phase, through the action of positive and negative charges, the flame retardant and polar small molecules are firmly controlled in the matrix, and its dispersion performance and compatibility are significantly improved, and a composite material with good compatibility and excellent mechanical properties is obtained, which is not easy to deform and has good rebound performance. And because of the synergistic effect of each component, the composite material has anti-ultraviolet function, is not easy to oxidize, and has excellent high temperature resistance. In Comparative Examples 2 and 4, since the flame retardant used is natural hydrotalcite, directly adding it to the matrix will cause the mechanical properties of the matrix to decline rapidly and the anti-aging ability to be significantly weakened. In Comparative Example 3, since no azo group of the self-crosslinking group is introduced, the anti-aging performance is significantly reduced. In general, the improvement in the mechanical properties and anti-aging performance of the composite material is the result of the synergistic effect of the components.

[0100] Table 2 Elasticity test and anti-aging performance test of polypropylene composite materials

[0101]

[0102]

[0103] 4) Flame retardant properties of polypropylene composites

[0104] The limiting oxygen index test was performed on the flat plate samples of Examples 1-4 and Comparative Examples 1-4, and the UL-94 combustion test results are shown in Table 3; it can be seen from the data in Table 3 that when natural hydrotalcite is added as a flame retardant, the flame retardant effect is poor and it is a combustible material. In Example 1-4, a hydrotalcite flame retardant having a nano-lamellar structure with a self-crosslinking group and a large number of anions is added. The hydrotalcite flame retardant is an organic-inorganic hybrid material having a carbon source, an acid source and a gas source. After being heated, the hydrotalcite flame retardant can expand and cover the surface of the substrate to protect the substrate, effectively block heat transfer, and reduce the thermal degradation rate, thereby isolating the fire source, delaying and interrupting the spread of flames. Phosphorus and nitrogen elements are grafted onto the hydrotalcite. During the combustion of the substrate, the flame retardant can produce acid substances such as phosphoric acid, promote the dehydration and carbonization of the substrate during the combustion process, accelerate the formation of the carbon layer, and the generated free radicals can quench the combustion chain reaction and prevent the combustion reaction from proceeding. The introduced nitrogen element can also produce non-flammable gas during the combustion process to dilute the oxygen concentration in the combustion system. The introduced hydrotalcite can increase the density of the carbon layer on the surface of the substrate, further improving the flame retardant properties of the substrate. The various components are synergistically flame retardant, giving the polypropylene composite material excellent flame retardant effect.

[0105] Table 3 Flame retardant properties test results of polypropylene composite materials

[0106] sample UL-94 combustion test grade Limiting oxygen index (%) Test Standards ASTM D3801 GB / T 2406.2-2009 Example 1 V-0 34.4 Example 2 V-0 33.8 Example 3 V-0 32.5 Example 4 V-0 31.6 Comparative Example 1 V-1 25.1 Comparative Example 2 - 19.9 Comparative Example 3 V-0 30.5 Comparative Example 4 - 17.3

[0107] It can be seen that the flame-retardant high-performance polypropylene composite material provided in the present application can be highly flame-retardant, has softness, flexibility, wear resistance and anti-aging properties, and is a flame-retardant high-performance polypropylene material.

[0108] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Any equal modifications and changes made to the technical solution of the present invention by ordinary persons in the art, as long as they do not deviate from the overall concept of the present invention, are still within the scope of the present invention.

Claims

1. A flame retardant high-performance polypropylene composite material, characterized in that: The flame retardant high-performance polypropylene composite material is prepared from the following raw materials in parts by mass: 100 to 120 parts of polypropylene matrix; 9 to 12 parts of flame retardant; 0.1 to 2.5 parts of antioxidant; Wherein, the polypropylene matrix is ​​a high molecular weight network structure polymer matrix obtained by polymerizing acrylic acid monomers into a first copolymer and cross-linking a block copolymer; The flame retardant is a hydrotalcite flame retardant with self-crosslinking groups.

2. The flame retardant high performance polypropylene composite material according to claim 1, characterized in that: The polypropylene matrix and its preparation method are specifically as follows: S001: In a reaction kettle, isooctyl acrylate, dimethylamino methacrylate, hydroxypropyl acrylate and n-dodecyl mercaptan are stirred evenly, and the temperature is slowly raised to 110-150° C. under nitrogen protection, and then an initiator azobisisobutyronitrile is added dropwise. After fully reacting for 150-200 minutes, acrylic acid is added and the reaction is continued for 100-150 minutes to obtain a first high molecular weight copolymer with an average molecular weight of 50,000-60,000, and hydroxyl groups and amine groups are grafted on the side chains; S002, adding the first copolymer and the block copolymer into a reaction kettle, raising the temperature to 200-220° C. under nitrogen protection, stirring at a speed of 500 rpm, dispersing the block copolymer in the high molecular weight first copolymer, and continuing the reaction for 60-80 minutes to obtain a high molecular weight network structure polymer matrix; The mass fraction of the dimethylamino methacrylate is 50-60 parts, the mass fraction of isooctyl acrylate is 10-20 parts, the mass fraction of acrylic acid is 20-30 parts, the mass fraction of hydroxypropyl acrylate is 50-60 parts, the mass fraction of n-dodecyl mercaptan is 1.0-2.5 parts, and the mass fraction of azobisisobutyronitrile is 2.0-4.0 parts.

3. The flame retardant high performance polypropylene composite material according to claim 1, characterized in that: in, The diamined block copolymer is obtained by modifying a styrene-butadiene-styrene block copolymer, and the specific preparation method thereof is as follows: S101, dissolving styrene-butadiene-styrene block copolymer in 150 mL of ethyl acetate, stirring at a temperature of 60 to 70° C., then dropping N,N-dimethylhexadecyl-1-amine into the completely dissolved styrene-butadiene-styrene block copolymer solution, reacting for 24 to 30 hours, and after the reaction, pouring the reaction solution into petroleum ether, precipitating and washing three times, and finally drying in a 60° C. oven to obtain a light yellow solid product; S102, dissolving N,N-dimethylformamide in deionized water at a temperature of 60°C, then slowly adding a light yellow solid product and reacting at 45°C for 30 hours; after the reaction is completed, filtering the impurities in the mixed solution to obtain a clear and slightly viscous filtrate, drying it in an oven at 35°C, and washing it with deionized water for multiple times to obtain a diamine block copolymer, the surface of the copolymer has a positive charge; wherein, the ratio of N,N-dimethylhexadecyl-1-amine to styrene-butadiene-styrene block copolymer is 1:10; the ratio of N,N-dimethylhexadecyl-1-amine to N,N-dimethylformamide is 1:

2.

4. The flame retardant high performance polypropylene composite material according to claim 1, characterized in that: The preparation method of the hydrotalcite flame retardant with self-crosslinking groups is specifically as follows: S201, drying the hydrotalcite at 80°C for 5 hours, then heating the hydrotalcite to 90°C in a mixed solution of nitric acid and sodium nitrate, stirring and soaking for 2 hours, after the reaction is completed, filtering, washing with anhydrous ethanol for 3 times, and drying at 80°C for 20 hours to obtain a hydrotalcite with an enlarged interlayer spacing; then adding glycine and deionized water to the hydrotalcite with an enlarged interlayer spacing, reacting at 60-80°C for 24 hours to obtain a suspension, wherein the volume ratio of nitric acid to sodium nitrate is 1:10, the concentration of nitric acid is 0.5 mol / L, and the concentration of sodium nitrate is 1.2 mol / L; the mass ratio of hydrotalcite to the mixed solution of nitric acid and sodium nitrate is 1:1; the mass ratio of glycine to hydrotalcite is 2-3:10; S202, adding dodecyl phosphate and inositol hexaphosphate to the suspension, stirring and reacting at 60-80° C. for 6-8 hours to obtain a reaction solution; adjusting the pH to neutral with citric acid, obtaining a product with a rotary evaporator, and drying the product in an oven at 80° C. for 12 hours to obtain a white solid containing a large amount of anions in the intercalation layer; The white solid is dispersed in deionized water to obtain a dispersion; the mass ratio of dodecyl phosphate, inositol hexaphosphate and hydrotalcite is 2-3:3-4:10; S203, adding azobenzene-4,4-dicarboxylic acid to deionized water, stirring evenly, adding sodium hydroxide solution, adjusting the pH value to 8.5, mixing the dispersion with the azobenzene-4,4-dicarboxylic acid after adjusting the pH, introducing N2 protection at room temperature, and reacting for 24 hours; filtering the liquid after the reaction to obtain a light yellow filter cake, washing the filter cake with deionized water and ethanol for 3-4 times respectively, drying in a vacuum oven at 60° C., and grinding to obtain a light yellow solid, which is a hydrotalcite flame retardant with a nano-lamellar structure having a self-crosslinking group, and the mass ratio of azobenzene-4,4-dicarboxylic acid to hydrotalcite is 1:

5.

5. The flame retardant high performance polypropylene composite material according to claim 1, characterized in that: The block copolymer is a styrene-butadiene-styrene block copolymer or a diamined block copolymer; the mass ratio of the block copolymer to the first copolymer is 2-4:10; and the molecular weight of the block copolymer is 60,000-70,000.

6. A method for preparing flame-retardant high-performance polypropylene, characterized in that: Add flame retardant, polypropylene matrix and antioxidant into a mixer, melt blend, mix at a temperature of 190-220°C, for 20-40 minutes, at a rotation speed of 100 rpm, and obtain a mixed product, which is flame retardant high-performance polypropylene.

7. A car mat, characterized in that: Made from the flame retardant high performance polypropylene according to any one of claims 1 to 6.